Professional training future teachers– choirmaster of teacher training - Юришева, Л. В.; Коржавих, І. М. (Scientific notes of the pedagogical department, 2017)
The article is devoted to a problem of professional preparation the future teacher–chorus of higher school. Authors analyses the peqularity of chorus preparation the students at the pedagogical establishment. Among the subjects musical cycle is conducting one of the main subjects. This is the most difficult subject in learning and studying and need further work in school. After working as a teacher of music junior specialist usually conducts and extracurricular activities, organizes choirs, vocal ensembles, various musical groups and, presenting musical art in the classroom, he can not do without choral conducting, for each class in the classroom – a small choir. Therefore, the rate of «Choral conducting» is one of the important places in the cycle of special subjects of the curriculum. Among the subjects musical cycle is conducting one of the main subjects. Conducting is an important part of musical performance in which most deeply scale and manifested his essence. Conducting – a type of music and performing arts, the management team of musicians in preparation and during a public performance of a musical work. Conducting done conductor. It provides ensemble harmony and excellence of performance, the team seeks to convey his artistic intentions performers, their understanding of the work. Art is based on a specially developed system of hand movements. The important role played in the process of conducting conductor and face, his eyes, facial expressions. Modern conducting requires a conductor of music and theoretical training, small ears, good musical memory, and the active, purposeful will. This is the most difficult subject in learning. The individual form of training in choral conducting class offers great opportunities for the full development of the individual musician. The purpose of conducting classes on the one hand, there is maximum disclosure and teaching creative abilities of students and other education its culture of independent learning of music. Students receive theoretical and technical training on conducting the choir. In class they are conducting mainly acquire necessary techniques and tools conductor technology, exploring diverse and very complex for conducting repertoire, but they have not sufficiently educated practical skills and ability to work with the choir. Future teacher and choirmaster – Head choir through gestures of conducting a chat with the erformers, ensuring coherence and ensemble performance excellence, transferring all their artistic intentions and creative idea of the composer. The main task of the teacher–hormeytra is attentive, the most accurate reproduction of the author’s intention, the ability to implement it. Nowadays future teacher– hormeystr – a highly educated, high intellectual level of general and musical development people, especially, has the ability to promote the best music samples of national and world music, reveal the content of the work, be professional interpreter and mentor–tutor creative team. An important disciplines in the education of future teacher–hormeystra is «Teaching method of conducting» which teaches students the theoretical and methodological foundations and practical setting, solving artistic problems, familiarization with all means and methods of conducting, education aesthetic qualities as musicians. The preparation of students of art specialties based on personality–oriented learning technologies is the leading position of modern education and necessitates the further development of technologies that would increase the effectiveness of the personality traits of students, ie, those qualities that are the logical result of studies in the future will be an important principle of professional teacher mastery of modern music.